2022
DOI: 10.1111/ijlh.13949
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell clonality testing for the diagnosis of T‐cell large granular lymphocytic leukemia: Are we identifying pathology or incidental clones?

Abstract: Introduction: T-cell clonality testing by T-cell receptor (TCR) gene rearrangement is key to the diagnosis of T-cell lymphoproliferative disorders such as T-cell large granular lymphocytic (T-LGL) leukemia. Benign clonal T-cell expansions, however, are commonly found in patients without identifiable disease, a condition referred to as T-cell clones of uncertain significance (T-CUS). In practice, T-cell clonality testing is performed for a range of reasons and results are often challenging to interpret given th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Given that several studies have demonstrated that clones constituting less than 20% of total lymphocytes or 400 cells/μL of blood are highly prevalent in patients without T‐cell malignancy and show no particular disease association, it is unclear if reporting these populations is necessary or even harmful (Chin‐Yee et al, 2022; Kroft & Harrington, 2022; Shi et al, 2020). The risk of overdiagnosis of a T‐cell malignancy is particularly higher in older patients presenting with unexplained cytopenia or post‐transplant patients who present with oligoclonal reactive cytotoxic T‐cell proliferations (Chin‐Yee et al, 2022; Kroft & Harrington, 2022). Most reactive T‐CUS cases are CD8+ or CD4+/CD8+ double‐positive, hence the decision to report these populations must be balanced with the risk of triggering unnecessary laboratory workup and misdiagnosis (Shi et al, 2020).…”
Section: Interpretation Of Results and Reporting Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that several studies have demonstrated that clones constituting less than 20% of total lymphocytes or 400 cells/μL of blood are highly prevalent in patients without T‐cell malignancy and show no particular disease association, it is unclear if reporting these populations is necessary or even harmful (Chin‐Yee et al, 2022; Kroft & Harrington, 2022; Shi et al, 2020). The risk of overdiagnosis of a T‐cell malignancy is particularly higher in older patients presenting with unexplained cytopenia or post‐transplant patients who present with oligoclonal reactive cytotoxic T‐cell proliferations (Chin‐Yee et al, 2022; Kroft & Harrington, 2022). Most reactive T‐CUS cases are CD8+ or CD4+/CD8+ double‐positive, hence the decision to report these populations must be balanced with the risk of triggering unnecessary laboratory workup and misdiagnosis (Shi et al, 2020).…”
Section: Interpretation Of Results and Reporting Considerationsmentioning
confidence: 99%
“…The incidence of T-CUS rises with age and given the normal function of T-cells, T-CUS is favored to represent reactive T immunoclones as they commonly exhibit features of activation and terminal differentiation including downregulation of CD5, CD2, CD3, and CD7 or upregulation of CD57 and CD56 (Case #12; Case #13).Given that several studies have demonstrated that clones constituting less than 20% of total lymphocytes or 400 cells/μL of blood are highly prevalent in patients without T-cell malignancy and show no particular disease association, it is unclear if reporting these populations is necessary or even harmful(Chin-Yee et al, 2022;Kroft & Harrington, 2022;Shi et al, 2020). The risk of overdiagnosis of a T-cell malignancy is particularly higher in older patients presenting with unexplained or post-transplant patients who present with oligoclonal reactive cytotoxic T-cell proliferations(Chin-Yee et al, 2022;Kroft & Harrington, 2022). Most reactive T-CUS cases are CD8+ or CD4+/CD8+ double-positive, hence the decision to report these populations must be balanced with the risk of triggering unnecessary laboratory workup and misdiagnosis(Shi et al, 2020).…”
mentioning
confidence: 99%